Pengelolaan Kawasan Bukit Kerang Kawal Darat dalam Pembangunan Berkelanjutan di Pulau Bintan - Defri Elias Simatupang (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
This paper examines management efforts in the Bukit Kerang Kawal Darat (BKKD) site area on Bintan Island, framing sustainable development goals (SDGs). There are indications that the BKKD site has not experienced any progress in the area, even though it has been more than ten years since the local government released the land. Identification of the potential of natural, human, and cultural resources in the BKKD area is important to be projected in the 2030 SDGs study. The SDGs study on archaeological sites is considered can help focus various parts of the most realistic and measurable by synthesizing based on Cultural Heritage Law, and Cultural Advancement Law. This paper uses inductive reasoning, starting with a discussion of all data from observations, interviews, and literature studies. The data was analyzed, interpreted, and designed as a simulation scoring method of readiness to achieve SDGs until 2030. A communication strategy is needed to produce a blueprint for measurable management stages within the framework of the SDGs until 2030 after the BKKD is registered as a cultural heritage. This is a practical and theoretical contribution to the study of Archeology for sustainable development.